Early onset, cold-induced lupus erythematosus panniculitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Lupus erythematosus panniculitis is a rare variant of lupus erythematosus characterized by a lymphocytic infiltrate prevailing in the deep dermis and subcutaneous fat tissue; it has been described exceptionally even in children. Here is presented a case that for its very early onset (8 months old) and its sensitivity to cold led to discuss the differential diagnosis from an Aicardi-Goutières type inherited skin disorder.